NEXT GENERATION PNEUMOCOCCAL CONJUGATE VACCINES EFFICACY AND EFFECTIVENESS IN DIFFERENT REGIONS OF THE WORLD - O. P. Kovtun (Voprosy Sovremennoj Pediatrii, 2014)
In the article latest published and presented data on 10- and 13-valent pneumococcal conjugate vaccines (PCV10 and PCV13) efficacy and effectiveness in different regions of the world overview is provided for prognosis of expected effect of Russian infants mass immunization as anti-pneumococcal vaccination has been included into the National immunization program in Russia since January 1, 2014. Based on analyzed data conclusion about PCV10 and PCV13 high effectiveness against invasive pneumococcal diseases (IPD) in 3+1 schedule has been made. PCV10 effectiveness against IPD in 2+1 schedule has been determined as 85,8% (Finland), for PCV13 — 100% (Norway). Serotype-specific effectiveness for IPD has been established for PCV10 only for serotypes 6B and 14, at the same time PCV13 serotype-specific effectiveness in 3+1 and 2+1 schedules has been established not only for PCV7-common serotypes, but for additional serotypes 1, 6А, 7F, 19А. In comparison with PCV7 efficacy and effectiveness against pneumonia and otitis media PCV10 has not shown additional benefits (in COMPAS and FinIP trials), at the same time PCV13 has demonstrated subsequent decreasing and additional effectiveness against these diseases (USA, Israel, France, Uruguay, Argentina, South Africa). Sustained and apparent statistically significant nasopharyngeal carriage reduction and herd effect (decreasing of IPD in non-vaccinated part of the population) have been established only for PCV13 (USA, England and Wales, Israel, France).